DESIGN, SYNTHESIS, AND ANTIMYCOBACTERIAL EVALUATION OF NOVEL PYRROLE-OXADIAZOLE MOLECULAR HYBRID AGAINST MYCOBACTERIUM TUBERCULOSIS - GANESH D MOTE; MAHESH G SARALAYA (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objective: To enhance the potency of susceptible Mycobacterium tuberculosis (MTB) and create novel derivatives for multidrug-resistant tuberculosis with a molecular hybrid of pyrrole with oxadiazole. Methods: A number of pyrrole-ligated oxadiazole molecular hybrid derivatives have been developed and produced in response to the bioisosteric similarities between isoniazid and pyrazinamide. Fourier transform infrared spectral data, mass spectrometry, and nuclear magnetic resonance were used to identify the target chemicals. The toxicity of the chosen ligands was assessed using human dermal fibroblast cell lines, and the in vitro Microplate Blue Alamar assay for antitubercular action of all the prepared compounds against the strain MTB H37Rv was assessed. Results: Every developed drug exhibited MTB inhibition, with a minimum inhibitory concentration (MIC) ranging from 3.12 to 50 μM. OP3 was the most effective MTB inhibitor among the drugs evaluated (MIC=3.12 μM). Conclusion: The current study’s findings indicate that the majority of the synthesized compounds exhibit an adequate range of molecular characteristics and are sensitive to MTB.